Of several branches essays from the Humanities Association Bulletin, - McCaughey, Gerald; Legris, Maurice (Heritage., 1968)
One of the most important functions of the Humanities Association of Canada is to bring together scholars from all disciplines of the humanities. The annual meetings of the Association choose themes designed to demonstrate the relatedness of the humanities/